Estratégias nutricionais em espécies congenéricas de cerrado e floresta estacional semidecídua - Paganeli, Bruno (2019)
The Brazilian cerrado, although is one of the hotspots for the biology conservation, is still under pressure. One of these is related to restoration practices. This hotspot presents a huge vegetative diversity, however with predominance of savannas physiognomies. These can be defined as tropical and subtropical biomes, where the herbaceous layer is almost continuous, interrupted only by shrubs and trees at varying densities, with growth and reproductive patterns linked to climatic seasonality and to the occurrence of fires. Since savannas appear in climates that also harbour forests, only the climate is not enough to explain the occurrence of the former. One of the factors postulated to explain the occurrence of savannas in areas whose climate allows forests is nutrientpoor soils, especially regarding nitrogen and phosphorus. We analyzed the strategies presented by congeneric species, one typical of the cerrado, and the other, seasonal forest through four treatments in hydroponic system: (1) complete Hoagland solution, (2) Hoagland solution but nitrogen, (3) Hoagland solution but phosphorus, and (4) Hoagland solution but nitrogen and phosphorus. We followed the individuals measuring how long cotyledons persist, the time for the appearance of the first pair of leaves, height, leaf area, specific leaf area, root:shoot ratio, aboveground biomass and total biomass. All tests were done using variance analyses. Our results suggest that cerrado and forest species are functionally distinct, already in the early stages of their development. Both, savanna and forest congeneric seedlings are limited by nitrogen. However, changes in functional traits due to phosphorus supply evidenced their distinct nutritional strategies. While the forest species improved their functional traits — evidencing the co-limitation and higher nutritional demand —, savannas species displayed signs of toxicity, expressed by the decrease of some attributes.